Academic Performance and Training of Library and Information Science (LIS) Undergraduates in Nigeria - Adeagbo, Omobolade; Mabawonku, Iyabo (Ghana Library Journal, 2022)
The study aims to determine the academic performance of Library and Information Science (LIS) undergraduates in Nigeria. There is an established relationship between academic performance and the quality of graduates from universities. Consequently, high academic performance will improve the quality of services that will be rendered by university graduates and vice-versa. This makes academic performance to be crucial for a professional course like Library and Information Science (LIS), therefore, necessitating the need for the evaluation of the academic performance of LIS undergraduates in Nigeria. Hence, a descriptive research design was adopted for this study and 14 universities from the federal, state and private categories in the six geopolitical zones of Nigeria, were enumerated. The proportionate sampling technique was adopted to select 40% of 200 to 400 Level LIS undergraduates in each university, making a total of 1526. Primary and secondary data collected were analysed using descriptive statistics like percentages, frequencies, pie charts and columns. The result showed that the academic performance of most of the LIS undergraduates was on average. Thus, much is still desired to improve the quality of the academic performance of the LIS undergraduates. Therefore, the need for an enhanced attitude toward learning to raise quality librarians and information professionals.